Students’ perceptions on the use of mobile application for English course (mapec) as a pre-language learning tool / Muhamad Izzat Rahim... [et al.] - Rahim, Muhamad Izzat; Kamarudin, Rafidah; Syed Aziz Baftim, Sharifah Sheha; Abd. Karim, Norfazlika; Zainal Arifin, Mazliyana; Ismail, Zainon (Universiti Teknologi MARA, Negeri Sembilan, 2019)
The use of mobile technology in language learning is rapidly growing. However, research on the use of mobile applications to foster English language learning particularly as a pre-language learning tool is still lacking. Therefore, the aim of this study is to investigate students’ perceptions on the use of Mobile Application in English Course (MApEC) as a pre-language learning tool to help prepare them for the actual class. A total of 29 Semester 1 Diploma students from a selected higher institution in Negeri Sembilan participated in the survey which was conducted to find out their perceptions on the use of MApEC as a whole, and as a pre-language learning tool to assist them prior to the actual English language class. The results indicate that participants were in favour of using MApEC and perceived that it is a very helpful pre-language learning tool. Therefore, the initial findings of this study can be used to further develop MApEC not only as a useful pre-language learning tool, but for English language learning as a whole.